Role of Liquid Biopsy as a Future Approach to Early Diagnosis and Management of Colorectal Cancer - Danardono, Edwin; Soediono, Mochammad Ridhwan; Amiruddin, Muhammad Tidar Abiyu (Indonesian Journal of Cancer, 2025)
Colorectal cancer (CRC) is a major global health challenge, ranking as the third most prevalent cancer worldwide. Traditional tumor biopsies are invasive and limited by issues such as tumor heterogeneity and the inability to perform repeated sampling. Liquid biopsy, a non-invasive diagnostic approach that analyzes biomarkers in bodily fluids like blood, offers an innovative solution to these challenges. By detecting circulating tumor DNA (ctDNA), circulating tumor cells (CTCs), exosomes, and tumor-educated platelets (TEPs), liquid biopsy allows for real-time tumor monitoring, early cancer detection, and personalized treatment strategies. This review explores the clinical applications of liquid biopsy in CRC, highlighting its potential for early detection, monitoring treatment response, and guiding customized therapies. Key biomarkers such as CEA, ctDNA, CTCs, and exosomal miRNAs offer insights into tumor dynamics and prognosis. While liquid biopsy shows promise for broad clinical use, challenges remain in standardizing methodologies and validating its efficacy through large-scale trials. Advances in technology and improved biomarker discovery are expected to enhance the accuracy and utility of liquid biopsy, making it a pivotal tool in CRC management and beyond.